The Diagnosis of Normocalcaemic Hyperparathyroidism is Strikingly Dissimilar Using Different Commercial Laboratory Assays - Kalaria, Tejas; Fenn, Jonathan; Sanders, Anna; Yates, Alexandra; Duff, Christopher; Ashby, Helen; Mohammed, Pervaz; Ford, Clare; Gama, Rousseau (Hormone and Metabolic Research, 2022)
We assessed the impact of intact parathyroid hormone (iPTH) and adjusted calcium analyses on Abbott, Roche and Siemens analytical platforms in the diagnosis of normocalcaemic primary hyperparathyroidism (NCPHPT). These assays are used by over 85% of clinical laboratories in the UK. Over five months, consecutive serum samples from outpatients with NCPHPT in the laboratory with Abbott assays were identified, aliquoted and stored at –80°C. Frozen aliquots were transported monthly to the other two laboratories. After thawing, samples were mixed and analysed immediately for calcium, albumin and iPTH in the laboratories with Abbott, Roche and Siemens analytical platforms. Adjusted calcium was calculated using the equation used in the respective laboratory. Diagnostic concordance of iPTH and adjusted calcium were assessed using manufacturer-provided assay-specific reference intervals and the pathology harmony reference interval respectively. Fifty-five patients with NCPHPT were identified using Abbott assays. Of these, 16 (29.1%) and 11 (20.0%) had NCPHPT, 9 (16.4%) and 13 (23.6%) had hypercalcaemic primary hyperparathyroidism, and 30 (54.6%) and 31 (56.4%) patients had normal results when analysed in laboratories with Roche and Siemens assays, respectively. The diagnosis of NCPHPT was strikingly different depending on the commercial assay used. There is a pressing need for iPTH assay harmonisation and robust reference intervals. Reference intervals may become invalid if an assay drifts, as exemplified by adjusted calcium in this study.
Keywords: parathyroid hormone (PTH); bone/calcium homeostasis; hyperparathyroidism; parathyroid